The complete Kwanzaa : celebrating our cultural harvest - Riley, D. Winbush (Dorothy Winbush) (New York : Castle Books, 2002)
A resource guide to Kwanzaa is organized around the seven principles and describes the traditions, practices, and cultural foundations of the holiday, providing celebrants with hundreds of suggestions for gift giving, food preparation, and more.
Introduction to Kwanzaa -- Principle 1: Umoja -- Principle 2: Kujichagulia -- Principle 3: Ujima -- Principle 4: Ujamaa -- Principle 5: Nia -- Principle 6: Kuumba -- Principle 7: Imani -- Kwanzaa's Karamu.
Includes bibliographical references (p. [371]-374) and index.
Keywords: Kwanzaa; African Americans -- Social life and customs